Implementing Chiral Three-Body Forces in Terms of Medium-Dependent Two-Body Forces - Holt, Jeremy W.; Kawaguchi, Mamiya; Kaiser, Norbert (Frontiers in Physics, 2020)
Three-nucleon (3N) forces are an indispensable ingredient for accurate few-body and manybody nuclear structure and reaction theory calculations. While the direct implementation of chiral 3N forces can be technically very challenging, a simpler approach is given by employing instead a medium-dependent NN interaction V med that reflects the physics of three-body forces at the two-body normal-ordered approximation. We review the derivation and construction of V med from the chiral 3N interaction at next-to-next-to-leading order (N2LO), consisting of a long-range 2π-exchange term, a mid-range 1π-exchange component and a short-range contact-term. Several applications of V med to the equation of state of cold nuclear and neutron matter, the nucleon single-particle potential in nuclear matter, and the nuclear quasiparticle interaction are discussed. We also explore differences in using local vs. nonlocal regulating functions on 3N forces and make direct comparisons to exact results at low order in perturbation theory expansions for the equation of state and single-particle potential. We end with a discussion and numerical calculation of the in-medium NN potential V med from the next-to-next-to-next-to-leading order (N3LO) chiral 3N force, which consists of a series of long-range and short-range terms.